Do lunar rover wheels sink equally on Earth and Moon? - A.J.R. Lopez-Arreguin; B. Gundlach; E. Stoll (Results in Physics, 2019)
There has been a long discussion on how the low-gravity effects that LRUs (Lightweight Rover Units) on the Moon will experience, can affect mission planning and surface operations. In particular, the sinkage observed when regolith soil layers collapse under a normal wheel load has been an important source of contradiction in the field of Terramechanics in the last years. In this short report we review the different authors opinions on this topic, examining in detail their definition, methods, and results.The sinkage of static wheels under lunar gravity could be less than on Earth (fixing body dimensions and soil), given the decreased normal load experienced by loose regolith. This is known as static sinkage. On the other hand, if the wheels are in permanent rotation, the effect of poor soil’s bearing capacity in lower gravities can lead to a deeper intrusion of the wheels as compared to the case on Earth (dynamic sinkage). The dynamic and static sinkage are low in lunar gravity and have more or less similar values in case the wheel surface is plane (smooth). However, if the wheel under test incorporates grousers, the lugs motion and soil’s bearing capacity would make the separate effect of dynamic sinkage to be much larger than in plane wheels. Finally, we evaluated a method that (at difference from previous models), can express more accurately the effect of static and dynamic sinkage in different gravity environments. The novel semi-empirical approach to estimate wheel penetration into soils assumes a dependency from wheel parameters, slip and terrain mechanical properties, demonstrating an improved goodness-of-fit (R2) from 91 to 99%, distinctly in a gravity interval of 16 up to 2 times the gravity on Earth. Keywords: Sinkage, Wheel, Rover, Gravity, terramechanics